Taxonomy and Molecular Studies of Rafflesia tuan-mudae Becc. (Rafflesiaceae) and Tetrastigma (Miq.) Planch. (Vitaceae) in Sarawak - Wan Nuur Fatiha, binti Wan Zakaria (Universiti Malaysia Sarawak (UNIMAS), 2019)
Rafflesia tuan-mudae Becc. (Rafflesiaceae) or known as Pakma locally, is one of the world’s most iconic species. In Sarawak, R. tuan-mudae is restricted to Western Sarawak and Central Sarawak (Belaga). Taxonomy, molecular phylogeny and genetic analyses of R. tuan-mudae were studied, as well as complete taxonomic revision and molecular phylogeny of Tetrastigma (Miq.) Planch. Six study sites were identified for R. tuan-mudae. Examination based on 181 individuals of R. tuan-mudae showed that species exhibited morphological plasticity, which could be ways of surviving in different environmental conditions. Nuclear ribosomal DNA (nrDNA) region was used to investigate genetic diversity, and genetic structure of 36 individuals of R. tuan-mudae collected across the sampled populations. A total of 12 polymorphic sites were obtained, resulting in 5 haplotypes. Overall haplotype and nucleotide diversity generated were h = 0.3063 ± 0.098 and π = 0.00066 ± 0.00029, respectively. Analysis of molecular variance (AMOVA) revealed that all variation was within populations, and no genetic structure observed among the populations. No significant effect of isolation by distance was detected from Mantel tests. High gene flow was recorded that lead to an indication that R. tuan-mudae populations were panmictic. Substantial morphological variations exhibited in R. tuan-mudae did not correspond to their geographic location. Phylogenetic analyses of R. tuan-mudae populations also revealed that R. tuan-mudae is monophyletic. A total of 11 Tetrastigma species is recorded in Sarawak, and a key is provided in this study. Tetrastigma rafflesiae and T. diepenhorstii are the host plants for R. tuan-mudae. Three DNA regions (one from nuclear genome and two from chloroplast genome) were used to test the monophyly of Tetrastigma species in Borneo and to investigate how well the treatment for Tetrastigma subgenera reflects natural groupings of species. Phylogenetic analyses based on 51 generated DNA sequences showed that Tetrastigma in Borneo is monophyletic and recognised two well-supported clades within subgenera Tetrastigma, which corresponded to section Tetrastigma and section Carinata. Tetrastigma diepenhorstii, the host plant of R. tuan-mudae formed a monophyletic group, indicating some degree of host-specificity and preferences. A comparison phylogeny between Rafflesia and Tetrastigma showed that Bornean Rafflesia would have broad potential host ranges, depending on their local population. In conclusion, DNA sequences could be used for DNA baseline data for future management and conservation of R. tuan-mudae and its host plant, Tetrastigma.